Family policies in colombia: nuances and approaches (2008)
This article is about the different approaches to “family policy” in Colombia, emphasizing on their different approaches and their relation to the particular social contexts on which their development occurs. The analysis of these different approaches will take as its starting point the pre-fixed models of “ideal family”, based on determinated ideas of economic development, sexual division of work and particular roles attributed to each gender. The article concludes with a comparison between the national program Families in Action of the Álvaro Uribe Vélez government, and the local program Family Policies: 2006-2008 developed in Bogotá DC while Luis Eduardo Garzón´s mayoralty.